The effectiveness of Social Media in Introducing the Jambi Taman Mini Indonesia Indah Pavilion to the Minelial generation - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Rivai, Achmad Iqbal; Bahri, Asep Syaiful (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Tourism is the industry that is most in demand by people today. In its development and implementation, the tourism sector has become one of the industrial sectors that contributes to the country's largest GDP. With the diversity of tribes and cultures owned by Indonesia, cultural tourism is a desirable tourist activity. Along with the development of social media, many tourism actors use it as a medium to disseminate information, especially among the millennial generation. Jambi Pavilion TMII utilizes social media as a medium to share information related to activities held at Jambi Pavilion. The data taken from this study is interview data that is used as a research subject. The research was conducted around Jambi Pavilion Taman Mini Indonesia Indah